Cytokines IL-1β and IL-10 are required for Müller glia proliferation following light damage in the adult zebrafish retina - Lu, Celine; Hyde, David R. (Frontiers in Cell and Developmental Biology, 2024)
Zebrafish possess the ability to regenerate dying neurons in response to retinal injury, with both Müller glia and microglia playing integral roles in this response. Resident Müller glia respond to damage by reprogramming and undergoing an asymmetric cell division to generate a neuronal progenitor cell, which continues to proliferate and differentiate into the lost neurons. In contrast, microglia become reactive, phagocytose dying cells, and release inflammatory signals into the surrounding tissue following damage. In recent years, there has been increased attention on elucidating the role that microglia play in regulating retinal regeneration. Here we demonstrate that inflammatory cytokines are differentially expressed during retinal regeneration, with the expression of a subset of pro-inflammatory cytokine genes upregulated shortly after light damage and the expression of a different subset of cytokine genes subsequently increasing. We demonstrate that both cytokine IL-1b and IL-10 are essential for Müller glia proliferation in the light-damaged retina. While IL-1b is sufficient to induce Müller glia proliferation in an undamaged retina, expression of IL-10 in undamaged retinas only induces Müller glia to express gliotic markers. Together, these findings demonstrate the essential role of inflammatory cytokines IL-1b and IL-10 on Müller glia proliferation following light damage in adult zebrafish.